Microalgae Based Wastewater Treatment: A Sustainable Approach - Ekta; Swapnil Chaturvedi (International Journal of Sustainability, 2026)
The global water crisis and strict environmental policies demand advanced wastewater treatment techniques that combine pollution control with resource recovery. Microalgae-based wastewater treatment has emerged as a sustainable biotechnological solution that aligns with circular economy principles by simultaneously eliminating contaminants and producing valuable biomass that can be converted into useful products. This review paper provides an in- depth assessment of the application of microalgae in treating municipal, industrial, and agricultural wastewater streams, outlining the mechanisms of nutrient uptake, organic matter degradation, removal of heavy metals, and pathogen inactivation. A critical evaluation of various cultivation systems is conducted, focusing on open high-rate algal ponds and closed photobioreactors, with particular attention to operational parameters, treatment efficiencies, and scalability. This review evaluates biomass harvesting technologies and valorization strategies aimed at the production of biofuels, biofertilizers, animal feed, and high-value biochemicals. Techno-economic analysis and life cycle assessment indicate the feasibility of cost-effective and environmentally friendly wastewater treatment. Despite their advantages, microalgae-based systems still face significant challenges such as risk of contamination, seasonal variability, high harvesting costs, and upscaling challenges remain significant barriers to commercial implementation. Recent advances in genetic engineering, development of microbial consortia, and process optimization through artificial intelligence offer promising solutions to these limitations. Case studies of pilot-scale implementations demonstrate practical effectiveness and identifies key factors that determine their success. Overall, the review concludes that microalgae-based systems represent a transformative approach in wastewater management, enabling simultaneous pollution mitigation, carbon sequestration, and resource generation. Broad implementation requires continued innovation in cultivation and harvesting technologies, supportive regulatory frameworks, and integrated biorefinery models that maximize economic returns while minimizing environmental impacts.
Keywords: Biomass Valorization; Microalgae; phytoremediation; resource recovery; wastewater treatment